Feminism and methodology : social science issues - Harding, Sandra G. (Bloomington, Indiana : Indiana University Press, 1987)
"Appearing in the feminist social science literature from its beginnings are a series of questions about methodology. In this collection, Sandra Harding interrogates some of the classic essays from the last fifteen years in order to explore the basic and troubling questions about science and social experience, gender, and politics."--Book cover
Introduction : Is there a feminist method? / Sandra Harding -- The social relation of the sexes : methodological implications of women's history / Joan Kelly-Gadol -- Introduction to Another voice : feminist perspectives on social life and social science / Marcia Millman and Rosabeth Moss Kanter -- Bias in psychology / Carolyn Wood Sherif -- Woman's place in man's life cycle / Carol Gilligan -- Introduction to Tomorrow's tomorrow : the Black woman / Joyce A. Ladner -- Women's perspective as a radical critique of sociology / Dorothy E. Smith -- The dialectics of Black womanhood / Bonnie Thornton Dill -- The family as the locus of gender, class, and political struggle : the example of housework / Heidi I. Hartmann -- Feminism, Marxism, method, and the state : toward feminist jurisprudence / Catharine A. MacKinnon -- The feminist standpoint : developing the ground for a specifically feminist historical materialism / Nancy C.M. Hartsock -- Conclusion : epistemological questions / Sandra Harding.
Includes bibliographical references and index.
Cover title: Feminism & methodology.
Online resource; title from PDF title page (EBSCOhost, viewed November 2, 2020).
English.
eBooks on EBSCOhost
Keywords: Social sciences; Feminism; Women social scientists; Women's rights; Women; Social Sciences; Women's Rights; Women; Feminism; Sciences sociales; Féminisme.; Femmes spécialistes des sciences sociales; Femmes -- Droits; Femmes; social sciences; feminism; women (female humans); SOCIAL SCIENCE -- Essays; Women's rights; Women; Feminism; Social sciences; Women social scientists; Frauenbewegung; Sozialwissenschaften; Aufsatzsammlung; Methode; Feminisme; Onderzoeksmethoden; Sociale wetenschappen; Femmes sociologues; Sciences sociales -- Méthodologie.; Féminisme.